Risk Factor Analysis for Cardiovascular Diseases in Pregeriatric Type 2 Diabetes Mellitus Subjects - U, Iyer (Journal of Medical Biomedical and Applied Sciences, 2014)
Pregeriatric type 2 diabetic subjects were enrolled to identify the various risk factors for cardiovascular diseas-es. The risk factors analysis on 120 diabetic subjects showed a high prevalence of overweight, obesity, abdo-minal obesity, hypertension and metabolic syndrome. Poor metabolic control as evident from HbA1c was seen in 60% of the diabetic subjects. Dyslipidemia was a common feature. Majority of the subjects had 4-8 risk fac-tors and the most prominent risk factors were overweight/obesity, abdominal obesity, hypertension and low HDL-C levels. The multiple risk factor scenario highlights the need to improve the lifestyle patterns of the pop-ulation to reduce the risk of cardiovascular diseases.